Cordycepin alleviates osteoarthritis by inhibiting chondrocyte ferroptosis via Keap1/Nrf2 axis - Jianlei Li; Zuo Lv (SpringerOpen, 2024)
Abstract Background Intervertebral disc degeneration (IVDD) is a prevalent condition known to contribute to lower back pain and various spinal disorders. The progression of IVDD is closely associated with cell ferroptosis. This study aimed to explore the therapeutic potential of a reactive oxygen species (ROS)-responsive hydrogel loaded with garlic extract for the inhibition of cell ferroptosis and the treatment of IVDD. Results The study encapsulated garlic extract within the hydrogel using physical entrapment and controlled the release of the extract through the ROS-responsive degradation of the hydrogel. Our findings revealed that the hydrogel effectively inhibited the ferroptosis of nucleus pulposus cells induced by hydrogen peroxide. Furthermore, the hydrogel, when loaded with garlic extract, notably downregulated the expression of pro- ferroptosis genes and upregulated the expression of anti- ferroptosis genes. Conclusions This study demonstrated that the hydrogel loaded with garlic extract significantly mitigated IVDD. These results highlight the promising potential of ROS-responsive hydrogel loaded with garlic extract as a viable treatment option for addressing IVDD.